2005
DOI: 10.1002/adma.200401078
|View full text |Cite
|
Sign up to set email alerts
|

All‐Optical Reversible Actuation of Photochromic‐Polymer Microsystems

Abstract: The morphology of the precursors and end products (crystals) were characterized by scanning electron microscopy (SEM) using a LEO Gemini 1530. The particle size and its distribution were determined from the SEM images with the help of the image measuring software ImageJ (Image Processing and Analysis, Wayne Rasband, National Institutes of Health, Bethesda, MD). Statistical analysis was performed using Origin (Origin Version 6.0, Microcal, Northampton, MA).Electrochemical Testing: Cathode samples were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
88
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 20 publications
0
88
1
2
Order By: Relevance
“…Photomechanical effects in polymeric materials have been examined by researchers for more than four decades [1]. Photochromic molecules (primarily azobenzene, although other molecules have been employed [2]) predominately are covalently bonded into the polymer network but at times have been added as a guest molecule [3,4]. The photomechanical response of these materials is strongly dictated by the structure of the polymer network.…”
Section: Open Accessmentioning
confidence: 99%
“…Photomechanical effects in polymeric materials have been examined by researchers for more than four decades [1]. Photochromic molecules (primarily azobenzene, although other molecules have been employed [2]) predominately are covalently bonded into the polymer network but at times have been added as a guest molecule [3,4]. The photomechanical response of these materials is strongly dictated by the structure of the polymer network.…”
Section: Open Accessmentioning
confidence: 99%
“…The MC aggregates, compared to the initial SP stereoisomers, have less effective partial molar volume. For this reason the polymer chains move closer to each other, 8 forming stronger inter-chain bonds and causing thus an increased stiffness of the sample. Upon VIS light and SP recovery there are no more MC isomers to form aggregates and the composite reverts to the original stiffness.…”
mentioning
confidence: 99%
“…A proper choice of the polymer and PMs is necessary in order to tailor effectively the mechanical properties of the material, due to the usually quite low efficiency of the photomechanical effect. So far the photochromic blends of SP and polymers were proposed for applications in rather few papers, e.g., the works of Athanassiou et al 8,9 and Fragouli et al, 10 where it was shown that SP-polymeric films (5 to 10% wt.) can change reversibly their volume due to the isomeric transformations of the embedded photochromic molecules, acting as light-controlled mechanical actuators or as optical gratings with reversible diffraction efficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations